The Impact of Resource Efficiency (5M) on Bore Pile Work Productivity - Soetjipto, Jojok Widodo; Wulandari, Diah Ayu Restuti; Damayanti, Alvira Yong Wenda (Rekayasa Sipil, 2025)
Bore pile foundation work is an important stage in construction that requires high productivity to achieve the desired time and quality targets. However, productivity is often hampered by constraints on 5M resources. This research aims to determine the number of working hours lost due to obstacles originating from each resource during the implementation of bore pile work. In this way, the impact of constraints on productivity can be identified and analyzed quantitatively. Then, baseline productivity is determined to serve as a reference for measuring the level of disruption. Next, a recapitulation of project constraints is carried out to identify the independent and dependent variables. The validity and reliability of the independent variables were tested before carrying out multiple linear regression analysis using four classical assumptions. Factor coefficient model calculations were carried out to measure the influence of each constraint factor on productivity. Expected productivity and disruption index are calculated to determine the disruption and loss of productivity. Lost working hours are calculated based on the accumulated impact of these obstacles. The research showed that during the 37 days of bore pile work with 198.8 working hours, the material factor significantly reduced productivity, with a loss of 2,743 hours. Machine and Money factors also contributed to a decrease in productivity of 2,088 hours and 1,31 hours respectively. Meanwhile, the Method and Man factors analysis could not be carried out because the observation data showed invalid results. The conclusion of this research reveals that the material factor is the main obstacle that influences the productivity of bore pile work, followed by the Machine and Money factors.